Z-Source Inverter for Photovoltaic Microgeneration - Almeida, Felipe A. F.; Guerra, Felipe [UNESP]; Serrao Goncalves, Flavio Alessandro [UNESP]; Batschauer, A. L.; Filho, AJS; Rech, C.; Brandao, D. I.; Martins, D. C.; Tedeschi, E.; Santos, E. C.; Marafao, F. P.; Antunes, FLM; et al. (Ieee, 2019)
The number of grid-connected photovoltaic systems has been growing in the world as a sustainable alternative for power generation. This paper presents a study of Z-source inverter applied to a low voltage residential photovoltaic microgeneration system. The ZSI topology is evaluated through the expressions related to its equivalent electrical circuits, with the differential of considering asymmetry and accounting for the ohmic losses due to the equivalent series resistances in the inductors and capacitors of the impedance network. In addition to the mathematical model of the ZSI converter, it is also presented a design methodology for the selection of impedance network elements. Finally, computational simulations considering the Simple Boost modulation technique are developed to evaluate the performance and effectiveness of the proposed system.
Keywords: Z-source Inverter; Grid-tie Microgeneration; Design of Impedance Network